Stages of hyperglycemia and common mental disorders in adults – The Brazilian Study of Adult Health (ELSA-Brasil) - Bessel, Marina; Vigo, Álvaro; Poyastro, Andréa; Nunes, Maria Angélica; Duncan, Bruce Bartholow; Schmidt, Maria Inês (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Diabetes mellitus and depressive disorders frequently coexist. However, this relationship has been little evaluated across stages of hyperglycemia and for a broad range of common mental disorders (CMDs). The objective here was to investigate the association between CMDs and stages of glycemia. DESIGN AND SETTING: Cross-sectional study conducted among civil servants aged 35-74 years participating in the ELSA-Brasil cohort. METHODS: CMDs were classified using the Clinical Interview Schedule – Revised (CIS-R). Glycemia was classified in stages as normal, intermediate hyperglycemia, newly classified diabetes or previously known diabetes, based on oral glucose tolerance testing, glycated hemoglobin (HbA1c), self-reported diabetes and medication use. Blood glucose control was assessed according to HbA1c. RESULTS: CMDs were most prevalent in individuals with previously known diabetes. After adjustments, associations weakened considerably and remained significant only for those with a CIS-R score ≥ 12 (prevalence ratio, PR: 1.15; 95% confidence interval, CI: 1.03-1.29). Intermediate hyperglycemia did not show any association with CMDs. For individuals with previously known diabetes and newly classified diabetes, for every 1% increase in HbA1c, the prevalence of depressive disorders became, respectively, 12% and 23% greater (PR: 1.12; 95% CI: 1.00-1.26; and PR: 1.23; 95% CI: 1.04-1.44). CONCLUSION: Individuals with previously known diabetes had higher CIS-R scores. Among all individuals with diabetes, worse blood glucose control was correlated with depressive disorder. No relationship between intermediate hyperglycemia and CMDs was observed, thus suggesting that causal processes relating to CMDs, if present, must act more proximally to diabetes onset.